DAMPAK PEMBERIAN KOMPENSASI, KOMPETENSI DAN MOTIVASI KERJA KONSULTAN PAJAK TERHADAP KINERJA (STUDI PADA PT. â€œXâ€ MANAGEMENT CONSULTANT SURABAYA) - RATNASARI, RENNI (Jurnal Akuntansi AKUNESA, 2016)
Abstract This study was conducted to determine the impact of the compensation, competence and motivation of tax consultants on employee performance PT. "X" Management Counsultant Surabaya. The study used a qualitative research approach with descriptive analysis. Data collection techniques such as interviews and document analysis. Interviews were conducted in three informants who works as a tax consultant at PT. "X" Management Counsultant Surabaya. Based on the results of the study concluded that with appropriate compensation and a good competence will increase work motivation of tax consultants that will impact on the high performance of a tax consultant, while if the compensation awarded has not been as expected by a tax consultant it will cause a decline in motivation and results in low performance.   Keywords: Compensation, Competency, Motivation, Performance, Tax Consultants